Proceedings of the 12th International Conference on Interaction Design and Children 2013
DOI: 10.1145/2485760.2485860
|View full text |Cite
|
Sign up to set email alerts
|

HygieneHelper

Abstract: In this paper, we describe a mobile system to support youth with autism spectrum disorder (ASD) learn about and track healthy hygiene behaviors, HygieneHelper. This mobile application was developed as the result of a multi-year action research project with six school districts and two county agencies all focused on using mobile technologies to help teens and young adults develop skills for independent living and employment. HygieneHelper includes multi-media learning modules, an interactive customizable interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Research on supporting people to manage other aspects of independent living has been reported. For example, Hayes and Hosaflook present a mobile system ('HygieneHelper') to support young people with ASD to learn about and track healthy hygiene behaviours, as a key skill for independent living and employment [3]. Research by Hourcade et al argues the need for supporting children with ASD to develop the social skills needed for independent living later in life, and presents a study evaluating the use of apps for encouraging social interaction in children with ASD, with positive results [5].…”
Section: Hci Research and Design For Independent Livingmentioning
confidence: 99%
“…Research on supporting people to manage other aspects of independent living has been reported. For example, Hayes and Hosaflook present a mobile system ('HygieneHelper') to support young people with ASD to learn about and track healthy hygiene behaviours, as a key skill for independent living and employment [3]. Research by Hourcade et al argues the need for supporting children with ASD to develop the social skills needed for independent living later in life, and presents a study evaluating the use of apps for encouraging social interaction in children with ASD, with positive results [5].…”
Section: Hci Research and Design For Independent Livingmentioning
confidence: 99%
“…Finally, follow-up studies are a way to also consider the ethics of taking away technologies that appear to be a real help for the user and which the user has come to depend on in everyday life. A lot of work within IDC and HCI in general focuses on evaluating assistive technologies and reporting results from these studies (e.g., [11,25]). However, what happens when this technology is taken away?…”
Section: The Value Of Follow-up Studiesmentioning
confidence: 99%
“…Researchers within the IDC community have for some years explored the potential of using technology to assist children with a variety of conditions (e.g., [11,25]). However, to date only limited research has focused on children with attention deficit hyperactivity disorder (ADHD), although ADHD is the most prevalent reported mental health diagnosis for children and teens [17], with a worldwide prevalence of approximately 5% [18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, learning self-control is one of the key aspects of SEL; it relies strongly on identifying a problematic situation and then to calm down before it is "too late" and emotions are already running high. One opportunity for technology in this setting can draw on the maturing HCI research on in-the-wild stress detection drawing on physiological data or speech prosody, for example, Hernandez et al [2011], Poh et al [2010], Pina et al [2014], Zeng et al [2009], and Ertin et al [2011]. We envision that such data could be used to support the learners in becoming aware of their heightened arousal (e.g., through a private tactile reminder such as FitBit wrist vibration), which can serve as a cue to start the self-calming/self-control mechanisms taught in class.…”
Section: Embedding Of Learnt Skills Into Other Settingsmentioning
confidence: 99%
“…For example, the MOSOCO project [Escobedo et al 2012;Tentori and Hayes 2010] exemplifies how mobile phones can help children on the autistic spectrum structure, but also their neurotypical peers, to structure and practise their social skills outside of lessons, and how the system can help elicit feedback from their peers. Similarly, HygieneHelper [Hayes and Hosaflook 2013] and SocialMirror [Hong et al 2012] help scaffold everyday activities for people with autism. Although the social aspects supported in these systems are relatively basic when compared to the full range of skills taught as part of SEL, they nonetheless raise the question about whether similar approaches might be possible for more complex behaviours.…”
Section: Embedding Of Learnt Skills Into Other Settingsmentioning
confidence: 99%